Penerapan Metode Multi-Objective Optimization on the Basic of Ratio Analysis (MOORA) dalam Keputusan Penerimaan Siswa Baru - Mesran Mesran, M.Kom; Juanda Hakim Lubis; Iwan Fitrianto Rahmad (Bulletin of Informatics and Data Science, 2022)
This research was made so that the school can easily select new students who are running as students in a school. This selection is done based on the criteria that have been determined by the school. To solve this problem, a decision support system is needed using the Multi-Objective Optimization Method on The Basic of Ratio Analysis (MOORA). this method is also quite easy to use and the results are good by obtaining the best value of 0.2296 with alternative A1 and followed by alternative A5 with a preference value of 0.1383. So that the decision support system by applying the MOORA method can solve problems in the selection of new students who are accepted or declared graduated with a systematic and precise selection. The MOORA method can also be used in people who really need it